2006
DOI: 10.1136/hrt.2005.074161
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptides in heart valve disease

Abstract: Synthesis and release of B-type natriuretic peptide (BNP) are increased in heart failure, and plasma concentrations provide important therapeutic and prognostic information. Recent studies have shown that BNP concentrations are also increased with disease of the mitral and aortic valves. The extent of the increase is broadly related to the severity of the valve abnormality and the degree of consequent cardiac remodelling. BNP concentrations appear to relate to prognosis in these patients and might have a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In cases where the combination of a PVL ≥ 2+ and a rise of NT‐proBNP by more than 1,640 ng L −1 was documented, the rate of death was 78% at 6 month and 89% at 12 months, respectively. It is well known that conversion from pressure overload to volume overload does ultimately lead to stretch of cardiomyocytes, which is a well‐known and strong release mechanism for natriuretic peptides from the heart .…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the combination of a PVL ≥ 2+ and a rise of NT‐proBNP by more than 1,640 ng L −1 was documented, the rate of death was 78% at 6 month and 89% at 12 months, respectively. It is well known that conversion from pressure overload to volume overload does ultimately lead to stretch of cardiomyocytes, which is a well‐known and strong release mechanism for natriuretic peptides from the heart .…”
Section: Discussionmentioning
confidence: 99%
“…12 Both have been used in the assessment of left ventricular dysfunction and have often been studied in valve conditions. 12,13,14 With regard to the use of brain natriuretic peptide as a marker of cardiac failure, in congenital and inflammatory diseases, only one study related to rheumatic cardiac disease was found by the authors. 15 Thus, the aim of the present study was to assess rheumatic mitral regurgitation in children and adolescents, addressing its clinical, electrocardiographic, and echocardiographic features, correlating these factors to each other and to the natriuretic peptide.…”
Section: Itral Regurgitation Is the Most Commonmentioning
confidence: 99%
“…In their study, there was no significant LV remodeling and sudden volume overload due to acute MR. Studies have shown that BNP is also produced in the atrium in addition to the main production site, ventricles. [26,27] On the other hand, there is dilatation of the LV with eccentric hypertrophy in chronic MR. Wall stress is normalized with the development of hypertrophy. Left ventricular function is not hyperdynamic as in the acute state, but is in a high-normal range.…”
Section: Resultsmentioning
confidence: 99%